Prognostic risk score of genotypic characteristics in oral cancer based on logistic regression model - Galíndez Costa, María Fernanda (2018)
Fil: Galíndez Costa, María Fernanda. Universidad Nacional de Córdoba. Facultad de Odontología. Departamento de Patología Bucal; Argentina.